The Influence of the Experiential Learning Model on the History Learning Outcomes of Class X Students of SMA Negeri 3 Woja - Khatimah, Husnul; Jannah, Nur; Irfan, M.; Firdaus, Afdal; Yuliarti, Yuliarti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the effect of the experiential learning model on the history learning outcomes of class X students of SMA Negeri 3 Woja in the 2024/2025 academic year. This type of research uses a pre-experimental research design with a quantitative approach and a one-group pretest-posttest design model. The population is all SMA Negeri 3 Woja students, totaling 178 students. The sample used was 18 class X students. The sampling technique used was purposive. Data were obtained through pretest and posttest then analyzed using the t-test. Based on the results of the initial test, an average of 56.94 was obtained, and the final test results obtained an average of 79.44. The final test data were analyzed using the Paired Sample t-test. The results of the t-test obtained a table of 1.746 and a count of -13.029. The table obtained was greater than the count at an error level of 5%. Based on the proposed hypothesis, there is an influence of the use of the experiential learning model on the history learning outcomes of students at SMA Negeri 3 Woja in the 2024/2025 academic year, so it can be concluded that Ha is accepted and Ho is rejected.